1872. Neurodevelopment in Apparently Normal Infants from Zika Virus Positive Pregnancies - Mulkey, Sarah B (Open Forum Infect Dis, 2019)
BACKGROUND: Congenital Zika syndrome (CZS) is seen in 5–12% of newborns from Zika virus (ZIKV)-infected pregnancies and includes severe neurologic abnormalities. However, the majority of ZIKV-exposed newborns do not have CZS. The risk for neurodevelopmental impairment for infants without CZS following in utero ZIKV is not well known. The objective was to determine whether infants without CZS exposed to ZIKV in utero, have normal neurodevelopment. METHODS: We performed a longitudinal study of neurodevelopment in Colombia for infants exposed to ZIKV in utero who had a normal fetal brain MRI (Mulkey et al, JAMA Peds 2019) and normal head circumference at birth. Infant development was assessed by the Warner Initial Developmental Evaluation of Adaptive and Functional Skills (WIDEA) and the Alberta Infant Motor Scale (AIMS) between 6 and 18 months of age. In-person training was done by a neurologist. The AIMS were video-recorded and scored centrally. Interrater reliability for the novel method of video-based AIMS was determined. WIDEA and AIMS scores were converted to Z-scores compared with normative samples. We also compared development between infants with normal and nonspecific findings on cranial ultrasound (US). RESULTS: Seventy-two non-CZS infants had neurodevelopmental tests; 40 were at a mean (SD) of 5.7 (0.9) months and 66 were at 13.5 (3.2) months of age. Thirty-four had two assessments. The total WIDEA, social cognition, and mobility domain scores became more abnormal with postnatal age (figure). The AIMS scores were similar to the normative sample. Three infants had an AIMS score < 2 SD’s below the norm. On cranial US, 19 infants (26%) had a nonspecific finding (lenticulostriate vasculopathy, choroid plexus cysts, subependymal cysts, and/or calcification). Infants with a US finding had a lower WIDEA mobility score than infants with normal US (P = .054). There was a trend toward lower AIMS scores in infants with US findings compared with infants with normal US (P = .26). AIMS Interrater agreement on video-based scoring was good (ICC = 0.73, 95% CI 0.42, 0.87). CONCLUSION: ZIKV-exposed infants without CZS are at risk for neurodevelopmental delay. Nonspecific cranial US findings may represent mild ZIKV-related injury. Long-term neurodevelopmental follow-up is important for all ZIKV-exposed infants. [Image: see text] DISCLOSURES: All Authors: No reported Disclosures.